2003
DOI: 10.1029/2003gl017451
|View full text |Cite
|
Sign up to set email alerts
|

Bimodal size distribution of C2–C4 dicarboxylic acids in the marine aerosols

Abstract: [1] Size distributions of C 2 -C 4 dicarboxylic acids in aerosols were studied in the marine boundary layer (MBL) of the central to western North Pacific as well as off the coasts of East Asia. C 2 -C 4 Diacids were mostly present in submicron particles over the coastal ocean, but they were relatively abundant in supermicron particles over the remote ocean. We found that the peak diameters for the concentration of C 2 -C 4 diacids in supermicron particles over the remote ocean were similar to that for the surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
72
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(77 citation statements)
references
References 18 publications
4
72
1
Order By: Relevance
“…particles which acted as cloud condensation nuclei and, thus, were processed by clouds. Similar observations were made by Mochida et al (2003a) showing bimodal mass distributions for both C 2 -C 4 dicarboxylic acids and sulphate, respectively. The modification of the larger size aerosol mode was ascribed to mass addition in clouds.…”
Section: Chemical Interactions With Clouds -Cloud Processingsupporting
confidence: 71%
“…particles which acted as cloud condensation nuclei and, thus, were processed by clouds. Similar observations were made by Mochida et al (2003a) showing bimodal mass distributions for both C 2 -C 4 dicarboxylic acids and sulphate, respectively. The modification of the larger size aerosol mode was ascribed to mass addition in clouds.…”
Section: Chemical Interactions With Clouds -Cloud Processingsupporting
confidence: 71%
“…Longer-chain dicarboxylic acids such as malonic and succinic acids produce oxalic acid via photooxidation reactions (Kawamura and Sakaguchi, 1999), and it is noted that succinate also exhibits a secondary peak in the 1.0 mm stage (in addition to a peak in the 0.32 mm stage). The oxalate mass size distribution is peculiar as it does not coincide with two previously documented modes: (i) it usually coincides with sulfate and its chief aqueous-phase precursor, glyoxylate (both of which have peaks in the 0.32 mm stage) (Sorooshian et al, 2007); and (ii) it also coincides with sea salt and other coarse crustal particle types due to partitioning to these surfaces and/or heterogeneous reactions during transport (Mochida et al, 2003). The observed oxalate mass size distribution might be explained by some combination of sources and pathways that produced malonate and nitrate, which also peak in the 1.0 mm stage, or by sinks such as iron-complexation effects, which have been documented in the regional cloud water (Sorooshian et al, 2013) and laboratory experiments of aqueous phase aerosol (Pavuluri and Kawamura, 2012, and references therein).…”
Section: Moudi Non-fire Resultsmentioning
confidence: 98%
“…Selective mixing is confirmed by the observation that hydrocarbons are rather associated with soot, whereas oxidized organics with sulfate particles (Lee et al, 2003). Mochida et al (2003) have studied the size distributions of C 2 -C 4 dicarboxylic acids in aerosols in the marine boundary layer. They found that over the remote ocean these substances were relatively abundant in the supermicron particles whereas over the coastal ocean they were mostly present in submicron particles.…”
Section: Observationsmentioning
confidence: 85%